The Nordic prescription databases as a resource for pharmacoepidemiological research—a literature review. (23rd May 2013) - Wettermark, B; Zoëga, H; Furu, K; Korhonen, M; Hallas, J; Nørgaard, M; Almarsdottir, AB; Andersen, M; Andersson Sundell, K; Bergman, U; Helin‐Salmivaara, A; Hoffmann, M; et al.
ABSTRACT Purpose All five Nordic countries have nationwide prescription databases covering all dispensed drugs, with potential for linkage to outcomes. The aim of this review is to present an overview of therapeutic areas studied and methods applied in pharmacoepidemiologic studies using data from these databases. Methods The study consists of a Medline‐based structured literature review of scientific papers published during 2005–2010 using data from the prescription databases in Denmark, Finland, Iceland, Norway, and Sweden, covering 25 million inhabitants. Relevant studies were analyzed in terms of pharmacological group, study population, outcomes examined, type of study (drug utilization vs. effect of drug therapy), country of origin, and extent of cross‐national collaboration. Results A total of 515 studies were identified. Of these, 262 were conducted in Denmark, 97 in Finland, 4 in Iceland, 87 in Norway, and 61 in Sweden. Four studies used data from more than one Nordic country. The most commonly studied drugs were those acting on the nervous system, followed by cardiovascular drugs and gastrointestinal/endocrine drugs. A total of 228 studies examined drug utilization and 263 focused on the effects and safety of drug therapy. Pregnant women were the most commonly studied population in safety studies, whereas prescribers' adherence to guidelines was the most frequent topic of drug utilization studies. Conclusions The Nordic prescription databases, with their possibility of record‐linkage, represent an outstanding resource for assessing the beneficial and adverse effects of drug use in large populations, under routine care conditions, and with the potential for long‐term follow‐up. Copyright © 2013 John Wiley & Sons, Ltd.